Studi Metodologi Tafsir Asy-Sya’rawi - Hikmatiar Pasya (Universitas Darussalam Gontor, 2017)
Understanding of Qur'an will always relate or have some correlation to the development of a human’s life. As stated by Umar ibn Khathab,